1986
DOI: 10.1159/000199329
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Therapeutic Effect of Wheat Bran, Mebeverine and Placebo in Patients with the Irritable Bowel Syndrome

Abstract: There is no generally accepted treatment in the irritable bowel syndrome (IBS), probably because of a lack of convincing therapeutic trials. In the present study, 120 outpatients with IBS participated in a prospective randomized therapeutic trial. According to a double-blind design, 40 patients received 400 mg/day mebeverine and 40 patients received a placebo. In an open branch of the trial, 40 patients were treated with 15 g/day wheat bran. The effects of treatment on symptoms were noted after 4, 8, 12 and 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0
3

Year Published

1988
1988
2012
2012

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 11 publications
0
69
0
3
Order By: Relevance
“…A European systematic review [66] identified nine placebo-controlled studies [71][72][73][74][75][76][77][78][79], but many did not use standardized diagnostic criteria and all were of low to intermediate quality since they were performed before the development of the Rome criteria for study design [80]. Abdominal pain was improved in seven of the studies [71,72,[74][75][76][77]79], bowel symptoms improved significantly versus placebo in two studies [77,79], and four reported global symptom severity improvement [71][72][73]76]. The authors concluded that there is sufficient evidence that antispasmodics may improve abdominal pain, but lack of evidence to support global symptom improvement [66].…”
Section: Clinical Efficacy Of Antispasmodicsmentioning
confidence: 99%
“…A European systematic review [66] identified nine placebo-controlled studies [71][72][73][74][75][76][77][78][79], but many did not use standardized diagnostic criteria and all were of low to intermediate quality since they were performed before the development of the Rome criteria for study design [80]. Abdominal pain was improved in seven of the studies [71,72,[74][75][76][77]79], bowel symptoms improved significantly versus placebo in two studies [77,79], and four reported global symptom severity improvement [71][72][73]76]. The authors concluded that there is sufficient evidence that antispasmodics may improve abdominal pain, but lack of evidence to support global symptom improvement [66].…”
Section: Clinical Efficacy Of Antispasmodicsmentioning
confidence: 99%
“…Various lines of evidence suggest that fiber supplementation may lead to deterioration in a proportion of patients, certainly in the secondary and tertiary care settings. Of the nine controlled trials addressing this issue, seven have found that fiber supplementation was not helpful in IBS patients [42][43][44][45][46][47][48][49][50]. One uncontrolled study of 100 patients with IBS reported that although 10 improved with fiber supplementation, 55 deteriorated, with bowel disturbance being adversely affected most often, followed by abdominal distension and pain [51].…”
Section: Dietary Fibermentioning
confidence: 99%
“…It is contentious whether dietary fibre improves the symptoms of IBS [19][20][21][22][23][24][25][26][27][28][29] although some limited trial data suggest constipation will benefit. However, gas may be increased and any effect on pain is equivocal with bran or bulking agents [30].…”
Section: Dietary Aids and Bulking Agentsmentioning
confidence: 99%